2021
DOI: 10.1007/s00330-021-08268-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a preoperative CT-based radiomic nomogram to predict pathology invasiveness in patients with a solitary pulmonary nodule: a machine learning approach, multicenter, diagnostic study

Abstract: Objectives To develop and validate a preoperative CT-based nomogram combined with radiomic and clinical–radiological signatures to distinguish preinvasive lesions from pulmonary invasive lesions. Methods This was a retrospective, diagnostic study conducted from August 1, 2018, to May 1, 2020, at three centers. Patients with a solitary pulmonary nodule were enrolled in the GDPH center and were divided into two groups (7:3) randomly: development (n = 149) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Since the concept of radiomics was formally proposed in 2012 ( 25 ), radiomics of the chest CT images has been widely used for the chemotherapy response prediction in non-small-cell lung cancer ( 26 ) and pathology invasiveness prediction in patients with solitary pulmonary nodules ( 27 ). Recently, radiomics also has been used in COPD for survival prediction ( 28 , 29 ), COPD presence prediction ( 30 ), and the COPD exacerbations ( 31 ). However, radiomics in COPD has not been extensively investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of radiomics was formally proposed in 2012 ( 25 ), radiomics of the chest CT images has been widely used for the chemotherapy response prediction in non-small-cell lung cancer ( 26 ) and pathology invasiveness prediction in patients with solitary pulmonary nodules ( 27 ). Recently, radiomics also has been used in COPD for survival prediction ( 28 , 29 ), COPD presence prediction ( 30 ), and the COPD exacerbations ( 31 ). However, radiomics in COPD has not been extensively investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the prognostic RBP-related signature was validated using four GEO datasets, which demonstrated that the prognostic signature was not restricted by different sequencing techniques and platforms. Previous studies have shown that a nomogram better predicts disease prognosis due to its multidimensional parameters (Huang et al, 2022;Luo et al, 2022). Thus, a nomogram was constructed in the present study to predict the 1-, 3-, and 5-year OS probability in NSCLC, and calibration plots of the nomogram showed high predictive accuracy.…”
Section: Figurementioning
confidence: 77%
“…Huang et al. ( 33 ) established a nomogram model to predict the pathological aggressiveness of isolated lung nodules based on clinical, intranodal, and perinodal radiomics. Vaidya et al.…”
Section: Discussionmentioning
confidence: 99%